ANALISIS CROWDFUNDING UNTUK ANAK PADA SITUS NUCARE.ID PERSPEKTIF AKUNTANSI SYARIAH - Novendi Arkham Mubtadi; Anggara Arkham Tsani; Ibnu Fajri (PSGA LP2M IAIN Pontianak, 2022)
The purpose of this study is to analyze crowdfunding programs for children in the perspective of sharia accounting. This research uses qualitative research with a case study approach. The sampling technique in this study used purposive sampling by taking existing programs on the NUcare.id site with 21 populations and 6 samples obtained. The results of this study are the crowdfunding program for children on NUcare.id which is campaigned by Nahdlatul Ulama is in accordance with the perspective of sharia accounting, which meets all aspects of Sharia Enterprise Theory. While the effectiveness of each program has not been effective because the percentage is less than one percent compared to the total donation target. Suggestions for the next researcher are the need for more in-depth analysis related to crowdfunding for children by adding data collection techniques in the form of in-depth interviews to stakeholders who are more technical in implementing the program so that the data produced is more accurate.